Relative performance of down conductor for lightning protecion system - Yeap, Kin Wai (2014)
The continuous development of lightning protection system is very essential to mankind due to the severity of damages caused by lightning strike. The numbers of skyscraper in the world are keeping on increase day by day due to globalization. The higher the building goes the more vulnerable of the building being stroked by lightning. Lightning protection system has been improved dramatically with time from the earliest method of Franklin rod to present widely used three methods of Protection Angle Method (PAM), Rolling Sphere Method (RSM) and Mesh Method. Air Terminal and down conductor played an important roles in a lightning protection system. Air Terminal will initiate an upward leader to meet with the lightning downward leader to form a path for the lightning to discharge it current. The current will then follow the path provided by the down conductor to safely discharge to ground.